Survival outcomes after surgical management of sporadic or familial adenomatous polyposis associated duodenal cancer. Issue 6 (10th August 2020) - Augustin, Toms; Moslim, Maitham A.; Cengiz, Turgut Bora; El‐Hayek, Kevin; Simon, Robert; Bhatt, Amit; Tang, Andrew; Burke, Carol A.; Matthew Walsh, Richard
Abstract: Background: Duodenal cancer is the second most common cause of cancer death in familial adenomatous polyposis (FAP) patients. In this study, we compare oncologic outcomes between sporadic and FAP‐associated duodenal cancer. Methods: In this retrospective study, all patients who underwent surgeries between 2000 and 2014 for either sporadic or FAP duodenal cancer were identified. The patients were grouped based on diagnoses and perioperative and survival outcomes were compared. Results: A total of 56 patients with duodenal cancer (43 sporadic, 13 FAP) who underwent surgery were identified. Pancreatoduodenectomy (PD) was the most common procedure performed. The overall median survival was 7.5 years (1 year: 92%; 5 years: 58.1%). FAP patients had earlier tumor, node, and metastasis stage, less margin involvement, less perineural, and angiolymphatic invasion but had a comparable survival to sporadic patients. The median survival for FAP duodenal cancer was 7.4 vs 9.6 years for sporadic ( P = .97) with similar utilization of adjuvant chemotherapy. Although not statistically significant, PD had an improved median survival compared to segmental duodenal resection (SDR) (9.6 years for PD vs 3.6 years for SDR, P = .17). Non‐periampullary location and presence of positive lymph nodes were significant predictors of mortality on multivariate analysis. Conclusions: FAP duodenal cancer has no survival advantage compared to sporadic duodenal cancer despite an improved stage of resection with extraampullary lesions having a worse survival.